1998
DOI: 10.1136/thx.53.8.677
|View full text |Cite
|
Sign up to set email alerts
|

Acute inhalation of cigarette smoke increases lower respiratory tract nitric oxide concentrations

Abstract: Background-Cigarette smoking is associated with a number of common pulmonary diseases including chronic airflow limitation and bronchial carcinoma. Lower respiratory tract (LRT) nitric oxide (NO) concentrations are reduced in habitual cigarette smokers between cigarettes, and although this finding has been implicated in the pathogenesis of smoking related disease, the underlying mechanisms are unclear. A study was undertaken to determine the nature and time course for changes in LRT NO concentrations following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 27 publications
6
43
1
2
Order By: Relevance
“…Several investigators routinely require subjects to wear noseclips during NO measurements [10,26,31,35], while others do not [17,21,36]. Without a noseclip, diffusion of NO through the nares as well as into the posterior nasopharynx is possible; with a noseclip only diffusion towards the pharynx can occur, and this would increase contamination with high nasal NO levels.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators routinely require subjects to wear noseclips during NO measurements [10,26,31,35], while others do not [17,21,36]. Without a noseclip, diffusion of NO through the nares as well as into the posterior nasopharynx is possible; with a noseclip only diffusion towards the pharynx can occur, and this would increase contamination with high nasal NO levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that inhalation of cigarette smoke transiently increased NO concentrations in the human lower respiratory tract. 13 Therefore, it would seem that NO is inhaled along with cigarette smoke, even in humans. Although such NO may have localized effects on the respiratory system, the results of the present study indicate that the net transient effect of cigarette smoking is actually to decrease NO in the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…They include sex and sexual hormones, body weight and age, circadian changes of respiratory function in health and disease, caffeine and alcohol, meals rich in nitrate, genetic background for some enzymes, upper respiratory tract infection, exercise, drugs (including inhibitors of NO synthases) and of course smoking [46,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73]. Moreover, FeNO levels in healthy subjects are influenced by atopy, i.e.…”
Section: Exhaled Nitric Oxidementioning
confidence: 99%